Successful use of TNFα blockade in a severe case of idiopathic non-granulomatous ulcerative jejunoileitis associated with thrombotic thrombocytopenic purpura. Issue 1 (8th February 2019) - Braun, Fabian; Suarez, Victor; Dinter, Johanna; Haneder, Stefan; Quaas, Alexander; Benzing, Thomas; Nierhoff, Dirk; Müller, Roman-Ulrich
Abstract : We describe the case of 50-year-old female patient who presented with severe gastrointestinal symptoms and progressive weight loss of unknown origin. Shortly after admission, she developed an acute flare of thrombotic thrombocytopaenic purpura (TTP) that had to be treated by plasma exchange therapy and rituximab administration. While the signs of TTP subsided, the gastrointestinal symptoms worsened with abdominal cramps, massive gastric retention, malnourishment and a stenosis due to extensive inflammation and wall thickening of the small bowel. Extensive diagnostic efforts yielded no specific cause, so the patient—based on the histopathological findings—was diagnosed with idiopathic non-granulomatous ulcerative jejunoileitis. Following a highly complicated clinical course over several months, successful remission of the inflammatory activity and recovery of the patient could be obtained by TNF-alpha blockade.